2007
DOI: 10.1016/j.pain.2006.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Placebo analgesia is accompanied by large reductions in pain-related brain activity in irritable bowel syndrome patients

Abstract: Previous experiments found that placebos produced small decreases in neural activity of pain-related areas of the brain, yet decreases were only statistically significant after termination of stimuli and in proximity to when subjects rated them. These changes could reflect report bias rather than analgesia. This functional magnetic resonance imaging (fMRI) study examined whether placebo analgesia is accompanied by reductions in neural activity in pain-related areas of the brain during the time of stimulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
185
2
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(229 citation statements)
references
References 26 publications
26
185
2
15
Order By: Relevance
“…Functional imaging studies using positron emission tomography and fMRI revealed that patients with IBS often have exaggerated activation of cerebral sensory areas, especially emotional areas of brain following visceral stimulation as compared to healthy subjects. [12][13][14][15][16][17][18][19][20] Evidence from these studies indicates differential activation of the anterior cingulate cortex (ACC), prefrontal cortex (PFC), thalamus, insular cortex, and other limbic brain regions during colorectal stimulation, heterotopic stimulation or rectal balloon distension in IBS patients compared with healthy subjects. [12][13][14][15]18 Furthermore, resting state fMRI study performed on IBS patients demonstrated increased spontaneous neuronal activity in visceral afferent processing regions, while decreased regional brain activity in cognitive and pain regulatory regions.…”
Section: Introductionmentioning
confidence: 99%
“…Functional imaging studies using positron emission tomography and fMRI revealed that patients with IBS often have exaggerated activation of cerebral sensory areas, especially emotional areas of brain following visceral stimulation as compared to healthy subjects. [12][13][14][15][16][17][18][19][20] Evidence from these studies indicates differential activation of the anterior cingulate cortex (ACC), prefrontal cortex (PFC), thalamus, insular cortex, and other limbic brain regions during colorectal stimulation, heterotopic stimulation or rectal balloon distension in IBS patients compared with healthy subjects. [12][13][14][15]18 Furthermore, resting state fMRI study performed on IBS patients demonstrated increased spontaneous neuronal activity in visceral afferent processing regions, while decreased regional brain activity in cognitive and pain regulatory regions.…”
Section: Introductionmentioning
confidence: 99%
“…The increases did not occur in the IBS group not given the verbal suggestion. Taken together, these studies of IBS patients reflect the conscious cognitive nature of this form of analgesia (7)(8)(9). After all, the patients have to hear the verbal suggestion, understand its meanings, retain a working memory of it, and develop expectations and feelings about reduced pain (which they can rate on scales), unlike the mechanisms of subliminally conditioned changes in pain described by Jensen et al (1).…”
Section: Consciously Evoked Placebo and Nocebo Effectsmentioning
confidence: 86%
“…Although all other aspects of the placebo procedures were the same, IBS patients given the verbal suggestion had much larger placebo effects than patients not given the suggestion (7,9). When both groups were compared in fMRI analyses of brain activity, only the group receiving the verbal suggestion showed large reductions in brain activity related to processing pain (7).…”
Section: Consciously Evoked Placebo and Nocebo Effectsmentioning
confidence: 98%
See 2 more Smart Citations